2015
DOI: 10.1103/physrevapplied.3.044010
|View full text |Cite
|
Sign up to set email alerts
|

Intensity- and Temperature-Dependent Carrier Recombination inInAs/InAs1xSbx

Abstract: Time-resolved measurements of carrier recombination are reported for a midwave infrared InAs=InAs 0.66 Sb 0.34 type-II superlattice (T2SL) as a function of pump intensity and sample temperature. By including the T2SL doping level in the analysis, the Shockley-Read-Hall (SRH), radiative, and Auger recombination components of the carrier lifetime are uniquely distinguished at each temperature. SRH is the limiting recombination mechanism for excess carrier densities less than the doping level (the lowinjection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 50 publications
1
30
0
2
Order By: Relevance
“…Samples are grown by molecular beam epitaxy using previously described techniques [6,9,10,13]. For all seven samples, the epitaxial layers consist of a GaSb buffer layer, a bottom 100-nm Al(As,Sb) barrier layer, an unintentionally doped and nominally 4-μm-thick T2SL absorber layer, a top 100-nm Al(As,Sb) barrier layer, and a 150-nm In(As,Sb) cap layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples are grown by molecular beam epitaxy using previously described techniques [6,9,10,13]. For all seven samples, the epitaxial layers consist of a GaSb buffer layer, a bottom 100-nm Al(As,Sb) barrier layer, an unintentionally doped and nominally 4-μm-thick T2SL absorber layer, a top 100-nm Al(As,Sb) barrier layer, and a 150-nm In(As,Sb) cap layer.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature-and carrier-density-dependent studies on MWIR InAs=InðAs; SbÞ T2SLs have shown that SRH recombination limits the MC carrier lifetime at low temperatures and low-injection carrier densities [5,6,[8][9][10]13]. The mid-band-gap SRH recombination centers identified in MWIR InAs=InðAs; SbÞ T2SLs have been previously reported to be at an energy approximately 250 meV below the valence-band edge of bulk GaSb [5,9].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This can be circumvented by Ga‐free T2SL InAs/InAsSb. The T2SL InAs/InAsSb have much longer SRH lifetimes than InAs/GaSb, but they also have much lower absorption coefficients, meaning that the dark current is improved, but quantum efficiency (QE) suffers . In this study, we examined the MWIR nBn photodetector with a T2SL InAs/InAsSb active layer with the incorporation of an AlAsSb barrier.…”
Section: Introductionmentioning
confidence: 99%